PALYNOLOGICAL ORIGIN, PHENOLIC CONTENT AND ANTIOXIDANT PROPERTIES OF GEOPROPOLIS COLLECTED BY MANDAÇAIA (MELIPONA MANDACAIA) STINGLESS - Silva, Paulo Ricardo da (2020)
The stingless bee Melipona mandacaia (Smith 1863) (mandaçaia) is found only in the region of Caatinga, Northeastern Brazil, in the states of Bahia and Pernambuco, near to São Francisco river. The aim of the present work was to determine the botanical origin and to evaluate the phenolic content and antioxidant properties (β-carotene/linoleic acid system, DPPH and ABTS scavenging) of mandaçaia geopropolis. 25 pollen types from 15 families were identified from the 9 geopropolis samples analyzed. Phenolic compounds content varied between all the geopropolis EtOH extracts, hexane, EtOAc and MeOH:H2O fractions. The main pollens found in the geopropolis samples were from the Leguminoseae family. This identification of meliponicultural plants is extremely important because it indicates the food sources used for the collection of nectar and pollen. Our results revealed that there is a strong relation between the phenolic compounds and the antioxidant activity. These results showed that total phenols of mandaçaia geopropolis may be responsible for the antioxidant activity with evidence that it's a rich source of phenols bioactive compounds with potential health benefits.